The Effect of Learning Motivation and Self-Efficacy on the Learning Engagement of Upper-grade Elementary School Students - Robbi Alfianisnaini Muslimin; Fauzatul Ma'rufah Rohmanurmeta; Atik Puji Astuti (Universitas Negeri Semarang, 2026)
This study aims to determine the influence of self-efficacy and learning motivation on the learning engagement of upper-grade elementary school students. This study employs a quantitative approach using a survey method. The sample consisted of 50 students selected using a saturation sampling technique. The research instruments included questionnaires on self-efficacy, learning motivation, and learning engagement, all of which had been tested for validity and reliability. Data analysis was conducted using multiple linear regression. The results indicate that self-efficacy has a positive and significant effect on learning engagement, with a p-value of 0.001 (<0.05). Learning motivation also has a positive and significant effect on learning engagement, with a p-value of 0.003 (<0.05). Furthermore, self-efficacy and learning motivation simultaneously had a significant effect on learning engagement with a significance value of <0.001. The coefficient of determination (R²) of 0.531 indicates that self-efficacy and learning motivation account for 53.1% of the variation in students’ learning engagement. The implications of this study suggest that teachers need to develop learning strategies capable of enhancing students’ self-efficacy and learning motivation to encourage their active engagement in the learning process. Thus, improving self-efficacy and learning motivation can serve as a means to enhance students’ learning engagement in the learning process.